Social Media Strategies for EFL Students: Enhancing Speaking Proficiency - Tasisa Dinsa, Mitiku; Teshome Taddese, Esayas (GIST – Education and Learning Research Journal, 2024)
Social media is a communication tool that facilitates EFL students to improve their speaking proficiency as it enables them to fully engage in oral communication, exchange information, and form long-term bonds in this modern era. This study intended to investigate EFL students’ social media as speaking strategies used vis-a-vis their speaking proficiency. A descriptive correlational design was used in this study. The participants were 70 English major students (second year and third year) at Wolkite University. To this end, data were collected using a questionnaire, the IELTS speaking proficiency test, and an interview to obtain reliable information. The findings showed that Facebook and YouTube were the most frequently used social media by learners, even though they felt less confident, more anxious, and less willing to communicate in English. The results also indicated that learners lacked awareness of how to purposefully use social media to address their speaking challenges. Conversely, the findings of this study showed that there was a positive correlation between the students’ use of social media and their speaking proficiency (r=0.461, p=.000, p>0.05). However, the students’ speaking proficiency was very poor because learners didn’t use social media for educational purposes, especially speaking skills. This might be because the learners did not use social networks effectively to promote their speaking proficiency. Therefore, it is suggested that in the learning of speaking skills, more attention should be paid to investigating the use of social media as a speaking strategy.